THE AFFECTIONS OF JOINTS MORE HAPPENED IN IRAQI PURE BRED ARAB HORSES - AL-Khazraji, Sinan A. (The Iraqi Journal of Veterinary Medicine, 2021)
This report was designed to study to affection of joints of the Iraqi Arabian horses limbs in vet. college clinic .The symmetrical in the size of joints and hooves in case of standing position . The clinical examination was done by palpation of fore and hind limbs from the sale of the hoof till the shoulder or hip joints. The results marked 68.35% of fetlock J.15.15% of coffin J.9.9%of hock J. and 6.6% of pastern joint. So it is means that the fetlock joint is more important than the other joints specially in fore limb e.i. one of the fore fetlock joints may lift the whole body weight .